Implementasi Qiyas Dalam Ekonomi Islam - Ahmad Masyhadi (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2020)
Qiyas is the fourth source of law in Islam, apart from the disagreements that occur among the scholars regarding the jujjahan of qiyas, this method of taking the law provides a wide way in which all the problems we face can be found a legal basis. In this way there is no reason for us to leave something without legal clarity. Although this is an excuse for those who reject qiyas even though they base their statements on the word of Allah SWT., But logically it is also impossible for something to be left without a decision, only that issue is not discussed in the text. However, the qiyas method as the fourth source of law must still prioritize the provisions of the three previous sources of law. Judging from the various kinds of 'illat, then the exploration of the law through the way of qiyas, must be carried out carefully and carefully. The dynamics of development and innovation of Islamic financial contracts in the Islamic economy, of course, will increasingly model according to the times. Therefore, it is a challenge that Muslim scholars must answer so as not to become a concern for the ummah when the application of Islamic financial contracts is packaged in a modern way so that on the one hand they must use the qiyas method to determine their legal status. This noble project, for example, can be formulated in an encyclopedia of contemporary sharia financial contracts that uses the qiyass method in determining the ashl and furu'nya from the perspective of Islamic law.